Experimental and numerical modelling of solid and hollow biomass pellets high-temperature rapid oxy-steam combustion: The effect of integrated CO2/H2O concentration. (1st November 2021) - Mostafa, Mohamed E.; Khedr, Yasmeen M.; Ling, Peng; Chi, Huanying; Hu, Song; Wang, Yi; Su, Sheng; Elsayed, Saad A.; Xiang, Jun
Highlights: Oxy-steam combustion of solid and hollow pellets was performed using plasma system. Combustion behaviour studied numerically using an upgraded single particle model. Experimental and numerical solutions fit perfectly for surface and center temperature profiles. At 30%H2 O/30%O2 /30%CO2 /10%N2, higher particle temperature was obtained. At high CO2 concentration, the char gasification reaction led to lower temperatures. Abstract: Oxy-steam combustion behaviour of rice straw (RS) pellets was studied at high temperatures experimentally in a new plasma combustion system and numerically using an upgraded one-dimensional unsteady-state single particle combustion model with a new homogeneous devolatilization volatile combustion and heterogeneous char oxidation sub-models under different O2 /H2 O/CO2 /N2 gas compositions. Experimental results showed that the temperature gradient profiles for both the surface and center decreased significantly when the steam was added to the gas mixture at 20 and 40%. At 30% H2 O, the heat consumption of the gasification reaction decreased which resulted in a higher particle temperature and a higher char oxidation reaction rate. Combustion characteristics for heating, ignition, devolatization, and combustion stages were obtained and confirmed through the time of recorded pictures by high-speed camera. The obtained experimental results were validated through fitting the measured values of surface and center temperature-time profiles, ignition time, final pellet diameter, and time for the maximum amount of released volatiles, under different H2 O and CO2 concentrations, with those predicted from the model solution. Also, the mass of the released volatiles and pellet diameter history were predicted from the model solution. Results of the model solution proved the reality and credibility of the measured and calculated experimental findings.